The clinical evidence for targeting human myeloid‐derived suppressor cells in cancer patients. Issue 2 (8th February 2017) - Tobin, Richard P.; Davis, Dana; Jordan, Kimberly R.; McCarter, Martin D.
Abstract : Review on clinical trials that directly or indirectly target MDSCs in cancer patients, and future directions for the field. Abstract : Myeloid‐derived suppressor cells (MDSCs) are a heterogeneous population of immature myeloid cells that represent a formidable obstacle to the successful treatment of cancer. Patients with high frequencies of MDSCs have significantly decreased progression‐free survival (PFS) and overall survival (OS). Whereas there is experimental evidence that the reduction of the number and/or suppressive function of MDSCs in mice improves the efficacy of anti‐cancer therapies, there is notably less evidence for this therapeutic strategy in human clinical trials. Here, we discuss currently available data concerning MDSCs from human clinical trials and explore the evidence that targeting MDSCs may improve the efficacy of cancer therapies.